1994
DOI: 10.1159/000120867
|View full text |Cite
|
Sign up to set email alerts
|

Treatment ofCraniopharyngiomas: The Multimodality Approach

Abstract: A Multimodality Protocol for the treatment of craniopharyngiomas, where stereotactic methods are used preferentially, give long-term results not inferior to those reported when microsurgical removal has been the first therapeutic choice. Case material, treated in accordance with this protocol, is presented in a long-term perspective. The features of the protocol are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 11 publications
0
22
0
4
Order By: Relevance
“…Several therapies have been proposed for patients with CPs, which allows the surgeon to choose the best way to treat each individual patient. 2 The best treatment for this type of tumor is complete removal with preservation of all endocrine and visual functions, which is achieved in a small number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several therapies have been proposed for patients with CPs, which allows the surgeon to choose the best way to treat each individual patient. 2 The best treatment for this type of tumor is complete removal with preservation of all endocrine and visual functions, which is achieved in a small number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported high recurrence rates despite apparently complete tumor resection and negative postoperative brain imaging, providing another strong argument for the concept of limited surgery combined with other therapeutic approaches, such as radiotherapy or intracystic catheter placement. 2,3,30,37,42,43,50,62,68,71,78,83,84,89,92,98 The surgical routes used to remove craniopharyngiomas have previously been transcranial approaches, whereas the transsphenoidal approach, in accordance with the indications defined by Guiot and Derome 35 in the early 1960s, was proposed initially for infradiaphragmatic lesions, with an enlarged sella, preferably in patients who had already developed panhypopituitarism. 72 More recently, technological progress and advances in terms of visualization permitted the extension of the microscopic transsphenoidal approach to a variety of suprasellar lesions.…”
mentioning
confidence: 99%
“…Essa substância é um antibiótico que atua em carcinomas de células escamosas, interferindo na replicação do DNA tumoral, levando à diminuição da produção de liquor e degeneração celular (32,34).…”
Section: Outras Opções Injeção Intratumoral De Bleomicinaunclassified
“…O efeito sobre a massa tumoral é principalmente sobre a parte cística, tendo pouco efeito sobre a parte sólida do tumor (34).…”
Section: Outras Opções Injeção Intratumoral De Bleomicinaunclassified